BIOSORPSI LOGAM Cu(II) DAN Cr (VI ) PADA LIMBAH ELEKTROPLATING DENGAN MENGGUNAKAN BIMASSA PHANEROCHAETE CHRYSOSPORIUM - Erriek A, Suprihatin, (Jurnal Teknik Kimia, 2009)
Heavy metal waste many there is in a few waste industry chemistry, for example at industry electroplating,metallurgy, smelting and others. At waste industry electroplating contains copper heavy metal and chromium which can cause contamination if thrown exceed boundary threshold enabled.This research method started with grows mushroom Phanerochaete Chyrsosporium in liquid medium with composition of peptone 20 gr/ltd an 40 gr/lt glucose incubation at temperature 350C during 6 day. Step of hereinafter is take 200 ml waste which concentration of Cu 2+ 5,7 mg/ltd an concentration of Cr6+ 137 mg/lt and hydrogen ion exponent 3,15 . Waste is boosted up its(the hydrogen ion exponent becomes 5 with nitration NaOH 0,1N 93,9 ml then is added with adsorbent 10,20,30,40 and 50 ml and incubation during 90,120,150,180 and 210 minutes. Then solution filtered and filtrate is analysed with spectrophotometer.Result of research is obtained [by] best condition at adsorbent volume 50 ml and adsorption time 210 minutes concentration of Cu2+ : 0,414 mg/lt and concentration of Cr6+ be 0,381 mg/lt.  Keyword :Biosorpsi, Phanerochaete Chrysosporium